T&T Clark companion to the Bible and film - Walsh, Richard G. (Bloomsbury companions, 2018)
List of Figures -- Introduction, Richard Walsh, Methodist University, USA -- Part 1: Contexts -- 1. Apocalypse Noir: The Book of Revelation and Genre - Michelle Fletcher, King's College London, UK -- 2. Counting Errors or Understanding Filmic History: Historiophoty and Bible Films - Anne Moore, University of Calgary, Canada -- 3. In the Creator's Image: Divine and Mundane Self-Reproduction in Science Fiction Films - Christopher Heard, Pepperdine University, USA -- 4. Murderous Archaeologists, Doubting Priests, and Mesopotamian Demons: The Bible in Horror and Adventure Cinema - Kevin M. McGeough, University of Lethbridge, Canada -- 5. Comedic Films and the Bible - George Aichele, Adrian College, USA -- 6. The First Seventy Years of Jesus Films: A Canonical, Source-Critical History - Jeffrey L. Staley, Seattle University, USA -- 7. Justice, Empire, and Nature: Deliverance, Covenant, and New Creation in East Asian Cinema - Sze-kar Wan, SMU Perkins School of Theology, USA -- 8. Biographical Approaches to Jesus Films: Prospects for Bible and Film, Dwight H. Friesen - Independent Scholar -- 9. Frames and Borders in Deuteronomy and Films on the Palestinian-Israeli Conflict - Brian Britt, Virginia Tech University, USA -- 10. "Blessed are the Peacemakers," The Deployment of Jesus in American and German Cinema During and After WWI - David J. Shepherd, Trinity College Dublin, Ireland -- 11. German Jesus Movies - Reinhold Zwick, Wilhems University, Munster, Germany -- 12. Once Upon a Time in the West...The Fate of Religion, the Bible, and the Italian Western - James G. Crossley, St. Mary's University Twickenham, UK -- Part 2: Theories -- 13. A Return to Form: Bible, Film Theory, and Film Analysis - Laura Copier, University of Amsterdam, the Netherlands -- 14. Seven Stages of Affect: Religion, Affect, and Mel Gibson's The Passion of the Christ - Robert Paul Seesengood, Albright College, USA -- 15. Rock Me Sexy Jesus?: Gender and Sexuality in Biblical Films Rhiannon Graybill, Rhodes College, USA -- 16. "Sooner Murder an Infant in Its Cradle": Wisdom and Childlessness in The Sweet Hereafter - Jay Twomey, University of Cincinnati, USA -- 17. Son of Man: A Case Study in Translation, Postcolonialism, and Biblical Film - Hugh Pyper, University of Sheffield, UK -- 18. American Slavery, Cinematic Violence, and the (Sometimes) Good Book - Rhonda Burnette-Bletsch, Eastern University, USA -- 19. Deleuze on Film, and the Bible - George Aichele, Adrian College, USA -- 20. There's a New Messiah in Town: The Messianic in the Western - Robert Paul Seesengood, Albright College, USA and Richard Walsh, Methodist University, USA -- 21. Lars von Trier's Dogville as a Cinematic Parable -Matthew S. Rindge, Gonzaga University, USA -- Part 3: Texts -- 22. Can We Try that Again? The Fate of the Biblical Canon on Film - Matthew Page, Bible and Film Blogger -- 23. Reversing the Hermeneutical Flow: Noah's Flood in Recent Hollywood Films - Adele Reinhartz, University of Ottawa, Canada -- 24. A Genre(s) Approach to The Prince of Egypt - P. Jennifer Rohrer-Walsh, Methodist University, USA -- 25. "What Child is This?" Reflections on the Child Deity and Generic Lineage of Exodus: Gods and Kings - Richard Walsh, Methodist University, USA -- 26. "What Shall We do with the Tainted Maiden?" Film Treatments of the Book of Esther - Deborah W. Rooke, University of Oxford, UK -- 27. Desert Tales: Mark and Last Days in the Desert - Tina Pippin, Agnes Scott College, USA -- 28. A Revolutionary Passion Film: Giovanni Columbu's Su Re (The King) - Lloyd Baugh, Gregorian University, Italy -- 29. A Deadly Daughter? Salome's Cinematic Afterlife - Caroline Vander Stichele, University of Amsterdam, the Netherlands -- 30. Belief is in the Eye of the Spectator: Beholding the Other Actor's Reaction - Jon Solomon, University of Illinois, USA -- 31. Ben-Hur (2016): Jesus Finds a Voice - Larry J. Kreitzer, University of Oxford, UK -- Filmography -- List of Contributors -- Modern Author Index -- Scripture Index -- Film Index